IMPACT OF THE PASSIVE/ACTIVE ULTRASONIC ACTIVATION ON THE ENDODONTIC IRRIGANTS EFFECTIVENESS - A REVIEW - Elvira Gyulbenkiyan; Angela Gusiyska (Peytchinski Publishing, 2023)
Introduction: various irrigation devices and chemical solutions are being developed and improved nowadays for better penetration deep into the complex root canal system. Activation of irrigating solutions enhances the solution effectiveness. Evidence in the literature suggests that ultrasonic irrigation is much more effective in this respect than syringe irrigation alone. Passive ultrasonic irrigation (PUI) and/or ultrasonically activated irrigation (UAI): nowadays, the two terms, PUI and UAI, are interchangeable in the literature and represent the same technique. Literature data have shown that combining ultrasonically activated NaOCl with EDTA results in significantly greater removal of the smear layer. Conclusion: the use of ultrasonic activation of the irrigating solution after root canal preparation significantly improves the removal of debris from hard-to-reach areas such as isthmuses, lateral canals and the apical delta.